Phenomenology and classification of food behavior disturbances (literature review, part I) - V. V. Romatsky; I. R. Syomin (Бюллетень сибирской медицины, 2006)
Literature data of epidemioloc character concerning prevalence of food behavior disturbances in the historical aspect are presented in the review. Modern diagnosis signs of this form of pathology are described, criteria of their perfection are discussed. The very high percent of comorbidity of food behavior disturbances with psychic and somatic disorders is noted by home and foreign authors.